Continuous Transfer Hydrogenation of Sugars to Alditols with Bioderived Donors over Cu–Ni–Al Catalysts. Issue 10 (29th April 2015) - Scholz, David; Aellig, Christof; Mondelli, Cecilia; Pérez‐Ramírez, Javier
Abstract The transfer hydrogenation of sugars to alditols with biobased alcohol donors was studied over hydrotalcite‐derived Cu6−xNixAl2 catalysts prepared by coprecipitation at different pH and featuring variable Cu/Ni ratios. Their evaluation, after in situ activation in pure H2 at 773 K, in the ethanol‐assisted upgrading of glucose in a continuous‐flow fixed‐bed reactor identified the solid synthesized at pH 9–10 and with Cu/Ni=1 as the best performer. Based on textural, structural, and redox analyses, this is related to an enhanced intermetallic interaction. Upon screening alternative donors, a sorbitol yield as high as 67 % was achieved with 1, 4‐butanediol. The catalytic system displayed a stable behavior during 48 h on stream and proved suitable to hydrogenate also fructose, mannose, xylose, and arabinose to the corresponding polyols (yields up to 65 %), thus standing as a more sustainable and economical alternative to Ru‐based catalysts for sugar reductive upgrading.